A water-heat combined supply system based on waste heat from a coastal nuclear power plant in northern China. (5th January 2022) - Tai, Chuanmin; Tian, Guansan; Lei, Wenjun
Highlights: A new water-heat combined supply system based on waste heat is proposed. The system realizes the simultaneous delivery of water and heat. The heating and water supply costs are 34.27 ¥/GJ and 4.08 ¥/m 3, respectively. The system has a higher exergy efficiency and a better economic benefit. Abstract: Based on the existing waste heat recovery technology and seawater desalination technology, a water-heat combined supply system based on waste heat from a costal nuclear power plant is proposed. The proposed system can improve the heating capacity of district heating systems and reduce the energy consumption of water-generating seawater reverse osmosis systems by recovering the waste heat from exhaust steam in a nuclear power plant. Through the simultaneous delivery of water and heat, the long-distance conveyance cost is reduced. The thermodynamic characteristics, energy-saving properties, environmental benefits, and economic efficiency of the proposed system are discussed and analysed. The results show that the heating capacity of the proposed system is increased by 55.5% compared to the original extraction steam heating load. The exergy efficiency is 16.07% higher and the heating cost is 12.32 ¥/GJ lower than those of traditional cogeneration district heating systems. The water supply cost of the proposed system is 2.95 ¥/m 3 lower than that of the conventional desalination water supply system. The current results of this study will be helpful in solving problems related to heat and water resource shortages and the high costs of long-distance heat and water conveyance in coastal areas.